1988
DOI: 10.1111/j.1365-2141.1988.tb02440.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour necrosis factor may contribute to the anaemia of malaria by causing dyserythropoiesis and erythrophagocytosis

Abstract: Among the unexplained changes caused by malaria in several host species, including man and mouse, are erythrophagocytosis and dyserythropoiesis. In order to see whether tumour necrosis factor (TNF) could contribute to these changes we injected recombinant human TNF intravenously into mice made very susceptible to this monokine by low density infection with a mouse malaria (Plasmodium vinckei) or prior injection of an extract of Coxiella burneti. Appreciable erythrophagocytosis, involving nucleated erythroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
144
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(152 citation statements)
references
References 21 publications
7
144
1
Order By: Relevance
“…8 Proinflammatory cytokines such as TNF, IL-1, and IL-6 are released by monocytes and suppress erythropoietin synthesis in adults with symptomatic malaria. [9][10] Similar observations have been made in children with persistent, asymptomatic Plasmodium falciparum malaria. 11 Reduced erythropoietin production or action might possibly explain reports 12 of reduced numbers of red cell precursors in acute malaria.…”
Section: Introductionsupporting
confidence: 64%
“…8 Proinflammatory cytokines such as TNF, IL-1, and IL-6 are released by monocytes and suppress erythropoietin synthesis in adults with symptomatic malaria. [9][10] Similar observations have been made in children with persistent, asymptomatic Plasmodium falciparum malaria. 11 Reduced erythropoietin production or action might possibly explain reports 12 of reduced numbers of red cell precursors in acute malaria.…”
Section: Introductionsupporting
confidence: 64%
“…Other contributory factors may include decreased red cell deformability, splenic phagocytosis and/or pooling, so they have an increased rate of clearance from the circulation. [10][11][12] Brooks et al 13 had reported the correlation of serum potassium, and the hemolysis of red blood cells in patients infected with malaria which agrees with the present study. According to the present study, a statistically lower plasma sodium level mean of 131.56±6.63 against the mean control level of 134.14±5.955 was observed.…”
Section: Discussionsupporting
confidence: 83%
“…The different values may be associated with environmental factors, socioeconomic status, or malaria immunity, among other factors (12)(13)(14). The study has further revealed that there were no statistically significant differences in granulocyte and lymphocyte counts between malaria-infected and noninfected children, and these findings are in agreement with many earlier reports (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) but disagree with the findings of George and Ewelike-Ezeani (17). In some cases of acute malaria, however, lymphopenia has been reported, but this has been associated with redistribution of lymphocytes with sequestration in the spleen (26,27).…”
Section: Discussionsupporting
confidence: 82%
“…In this study, significantly lower values of haematocrit and haemoglobin concentration have been observed in malaria-infected children compared to the controls, and these findings are in agreement with previous reports (6,11,17). Anaemia in malaria, however, is associated with a combination of haemolysis of parasitised red blood cells, accelerated removal of both parasitised and innocently unparasitised red blood cells, depressed and ineffective erythropoiesis due to tumour necrosis factor alpha, anaemia of chronic disease, and splenic phagocytosis or pooling (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%